Answer:
200,000
Step-by-step explanation:
its easy and simple lol
The definition is pretty simple:
![(f+g)(x) = f(x)+g(x)](https://tex.z-dn.net/?f=%20%28f%2Bg%29%28x%29%20%3D%20f%28x%29%2Bg%28x%29%20)
So, we only have to sum the expressions:
![f(x)+g(x) = 2x+4 - \dfrac{1}{5}x-3 = \dfrac{9}{5}x+1](https://tex.z-dn.net/?f=%20f%28x%29%2Bg%28x%29%20%3D%202x%2B4%20-%20%5Cdfrac%7B1%7D%7B5%7Dx-3%20%3D%20%5Cdfrac%7B9%7D%7B5%7Dx%2B1%20)
To prove a similarity of a triangle, we use angles or sides.
In this case we use angles to prove
∠ACB = ∠AED (Corresponding ∠s)
∠AED = ∠FDE (Alternate ∠s)
∠ABC = ∠ADE (Corresponding ∠s)
∠ADE = ∠FED (Alternate ∠s)
∠BAC = ∠EFD (sum of ∠s in a triangle)
Now we know the similarity in the triangles.
But it is necessary to write the similar triangle according to how the question ask.
The question asks " ∆ABC is similar to ∆____. " So we find ∠ABC in the prove.
∠ABC corressponds to ∠FED as stated above.
∴ ∆ABC is similar to ∆FED
Similarly, if the question asks " ∆ACB is similar to ∆____. "
We answer as ∆ACB is similar to ∆FDE.
Answer is ∆ABC is similar to ∆FED.
Answer:
no
Step-by-step explanation:
y = –5x + 4
Substitute the point into the equation
0 = -5(4) +4
0 = -20+4
0 = -16
This is not true so it is not a solution to the equation